P04.12 Characteristics of IDH-mutant gliomas with non-canonical IDH mutations. (6th September 2019) - Poetsch, L; Dehais, C; Frénel, J; Siegfried, A; Lacomme, S; Seizeur, R; Larrieu-Ciron, D; Cappellen, D; Loussouarn, D; Ferec, C; Eimer, S; Carpentier, C; et al.
Abstract: BACKGROUND: About 10% of IDH-mutant gliomas harbor non-canonical IDH mutations (non-R132H IDH1 and IDH2 mutations). The aim of the present study was to analyze the characteristics of these gliomas in comparison to those of IDH1 R132H mutant gliomas. MATERIAL AND METHODS: We retrospectively analyzed the characteristics of a multicentric series of 161 gliomas with non-canonical IDH mutations and compared them to those of consecutive series of 109 IDH1 R132H mutant gliomas. Medical, radiological and pathological were reviewed. RESULTS: Median age at diagnosis was 35 years in gliomas with a non-canonical IDH1 mutation, 42 years in those with an IDH2 mutation and 44 years in those with an IDH1R132H mutation. A familial history of cancer was more frequent in gliomas with a non-canonical IDH mutation than in those with an IDH1 R132H mutation (22, 3% vs 5, 5%, p<0.05). In both IDH1 R132H-mutant and non-canonical IDH-mutant gliomas the most frequent location was the frontal lobe. Yet, compared to IDH1R132H-mutant gliomas those with a non-canonical IDH mutation had more frequently an infratentorial location (5, 5% vs 0% p<0, 05) and were more frequently multicentric (4, 9%, versus 0.9%, p<0.05). Compared to IDH1R132H-mutant gliomas, gliomas with a non-canonical IDH1 mutation were more frequently astrocytomas (65.7% vs 45%, p<0.05) while those with an IDH2 mutation were more frequently oligodendrogliomas (82% vs 55%, p<0.05). The median overall survival in IDH1 R132H-mutant and non-canonical IDH-mutant gliomas was similar (122 versus 120 months). CONCLUSION: Gliomas with non-canonical IDH mutations are associated with distinct clinical, radiological and histological characteristics. Their prognosis, however, is similar to that of gliomas with canonical IDH mutations.